Electro-thermal treatment optimization of high concentration ammonia nitrogen by gaseous oxidation in liquid phase (GOLP) - Cao, Li Mei (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
This study is focused on optimizing the treatment parameters for high concentration ammonia using gaseous oxidation in liquid phase (GOLP). The conversion of ammonia was achieved electrothermally over mono-crystalline silicon supported CoOx catalyst. The experimental results demonstrated that factors including the co-anions, pH of the solutions, air flowrate and the current showed apparent influences on the ammonia removal. The higher the Cl(-) concentration and/or current, the better the efficiency of ammonia degradation. The increase of the air flowrate would increase the ammonia removal accordingly. And it was also observed that the pH declined during the ammonia conversion, and the neutral and alkaline pH were beneficial to the ammonia removal. The preliminary cost analysis based on lab data was also provided for future reference